2004
DOI: 10.1097/01.sap.0000123901.06133.b7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Aesthetic Satisfaction Following TRAM and Implant Breast Reconstruction

Abstract: Aesthetic satisfaction after breast reconstruction is highly influenced by the presence of nipple-areolar reconstruction and less so by age, timing of reconstruction, adjuvant therapy, or free flap procedures. The type of reconstructive procedure is a significant variable only in unilateral reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 22 publications
2
36
1
2
Order By: Relevance
“…Numerous studies have shown that patients who undergo postmastectomy, implant-based reconstruction after the receipt of preoperative chest wall irradiation have a higher incidence of complications, including capsular contracture, 19,[24][25][26] and that the receipt of postmastectomy adjuvant radiotherapy is correlated with both the development of complications and increased patient dissatisfaction. [27][28][29][30] Thus, the determination of effect size herein allowed clinically meaningful comparisons to be made between the effects of a known entity (such as postmastectomy radiotherapy) versus other clinical variables (such as implant type) that may have an impact on patients' satisfaction with their reconstructed breasts.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that patients who undergo postmastectomy, implant-based reconstruction after the receipt of preoperative chest wall irradiation have a higher incidence of complications, including capsular contracture, 19,[24][25][26] and that the receipt of postmastectomy adjuvant radiotherapy is correlated with both the development of complications and increased patient dissatisfaction. [27][28][29][30] Thus, the determination of effect size herein allowed clinically meaningful comparisons to be made between the effects of a known entity (such as postmastectomy radiotherapy) versus other clinical variables (such as implant type) that may have an impact on patients' satisfaction with their reconstructed breasts.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy after mastectomy but before reconstruction has not been shown to increase complications after autologous reconstruction (25); however, not all studies are in agreement (26,27). Certain studies show that postoperative radiotherapy to the breast reconstructed with a deep inferior epigastric perforator flap (DIEP) or transverse rectus abdominis myocutaneous (TRAM) flap has no effect on the reconstruction (28,29), while several others show a considerable negative effect on the final results of autologous reconstruction (24,26,(30)(31)(32)(33)(34).…”
Section: The Effect Of Radiotherapy On Breast Reconstructionmentioning
confidence: 99%
“…Por lo tanto, es muy difícil evaluar de forma científica estos aspectos en lo relativo a los resultados obtenidos en una reconstrucción mamaria, si bien en la actualidad, muchos estudios tienden a centrarse en la valoración de este aspecto. En este sentido, la tendencia actual de los estudios sobre el tema centran la atención en valorar los índices de satisfacción logrados con la reconstrucción realizada (6)(7)(8)(9)(10)(11).…”
Section: Discussionunclassified